Synthesis of N-methylated unsymmetric porphyrinoids with restricted N-centered chirality from chlorophyll-a. Issue 48 (9th December 2020) - Kawamoto, Yuki; Nagano, Yasunobu; Kitagawa, Yuichi; Tamiaki, Hitoshi
Abstract : N -Centered chiral stereoisomers of regioselectively N -methylated chlorophyll- a derivatives with a cationic distorted π-skeleton were successfully separated. Abstract : Regioselectively N -methylated chlorophyll- a derivatives were prepared as their cationic and hydrophilic species. Both their epimerically pure samples at the chiral methylated nitrogen atom were obtained, and the stereochemistry was proposed by circular dichroism spectral analysis. This is the first example for restricted N -centered chirality in an unsymmetric chlorin core.